Synchronized electrochemical detection of hydroquinone and catechol in real water samples using a Co@SnO2–polyaniline composite. Issue 15 (29th March 2023) - Saleem, Qasar; Shahid, Sammia; Javed, Mohsin; Iqbal, Shahid; Rahim, Abdur; Mansoor, Sana; Bahadur, Ali; Awwad, Nasser S.; Ibrahium, Hala A.; Almufarij, Rasmiah S.; Elkaeed, Eslam B.
Abstract : The sensors are effectively used in the determination of Hq and Cat in a real water sample. Abstract : The conductive composite Co@SnO2 –PANI was successfully synthesized using hydrothermal/oxidative synthesis. Using differential pulse voltammetry, a glassy carbon electrode modified with a CoSnO2 –PANI (polyaniline)-based electrochemical biosensor has been created for the quick detection of two phenolics, hydroquinone (Hq) and catechol (Cat). Differential pulse voltammetry (DPV) measurements revealed two well-resolved, strong peaks for GCE@Co–SnO2 –PANI, which corresponded to the oxidation of Hq and Cat at 275.87 mV and +373.76 mV, respectively. The oxidation peaks of Hq and Cat mixtures were defined and separated at a pH of 8.5. High conductivity and remarkable selectivity reproducibility was tested by electrochemical impedance spectroscopy, chronoamperometry, and cyclic voltammetry techniques in standard solution and real water samples. The proposed biosensor displayed a low detection limit of 4.94 nM (Hq) and 1.5786 nM (Cat), as well as a large linear range stretching from 2 × 10 −2 M to 2 × 10 −1 M. The real-sample testing showed a good recovery for the immediate detection of Hq (96.4% recovery) and Cat (98.8% recovery) using the investigated sensing apparatus. The synthesized biosensor was characterized by XRD, FTIR, energy dispersive spectroscopy and scanning electron microscopy.